2021
DOI: 10.1186/s40104-021-00613-y
|View full text |Cite
|
Sign up to set email alerts
|

TLR7/8 signalling affects X-sperm motility via the GSK3 α/β-hexokinase pathway for the efficient production of sexed dairy goat embryos

Abstract: Background Goat milk is very similar to human milk in terms of its abundant nutrients and ease of digestion. To derive greater economic benefit, farmers require more female offspring (does); however, the buck-to-doe offspring sex ratio is approximately 50%. At present, artificial insemination after the separation of X/Y sperm using flow cytometry is the primary means of controlling the sex of livestock offspring. However, flow cytometry has not been successfully utilised for the separation of X… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…In 2022, Huang [ 20 ] combined R848 with an alkaline semen diluent, achieving the successful isolation and enrichment of goat X sperm. This sex control technique, relying on the R848 activation of X sperm TLR7/8, was successfully validated in several mammals, including mice, cattle, and sheep, confirming the robustness of this sex control technology [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In 2022, Huang [ 20 ] combined R848 with an alkaline semen diluent, achieving the successful isolation and enrichment of goat X sperm. This sex control technique, relying on the R848 activation of X sperm TLR7/8, was successfully validated in several mammals, including mice, cattle, and sheep, confirming the robustness of this sex control technology [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 79%
“…The findings of Umehara [ 17 ] and Renfa [ 19 ] have shown that, after sperm treatment with R848, highly motile Y-bearing sperm are primarily located in the upper layer, while the lower layer predominantly contains slow-moving X-bearing sperm. To investigate whether the treatment of sperm with dsRNA-40 or dsRNA-DR can alter the ratio of X/Y sperm in the upper and lower layers, this study employed quantitative PCR based on the X-chromosome-specific gene Akap4 and the Y-chromosome-specific gene ddx3y to assess the percentage of Y and X sperm in the upper and lower layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testis samples were performed immunofluorescence as described (Ren et al, 2021). Briefly, the sections were deparaffinized, rehydrated, and infiltrated with 0.5% Triton X-100 for 10 min.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Owing to their environmental adaptability, these goats can increase the income of farmers. Moreover, the nutritional value of goat milk is high owing to its ease of digestion and absorption (Ren et al, 2021). This makes the dairy goat industry a major player in the dairy industry (Clark and Mora García, 2017).…”
Section: Introductionmentioning
confidence: 99%